HUBUNGAN ASUPAN ZAT GIZI MAKRO DAN PEMBERIAN MAKANAN TAMBAHAN TERHADAP STATUS GIZI BALITA USIA 6-23 BULAN DI PUSKESMAS CIRIMEKAR - Waruwu, Berliani Prastika Nibenia (SINERGI : Jurnal Riset Ilmiah, 2025)
Indicators of children's nutritional status are very important for monitoring the crucial phases of optimal growth and development. Bogor Regency is one of the regencies in West Java that still faces undernutrition issues. In 2023, there were 434 toddlers who experienced cases of undernutrition. Specifically for the working area of the Cirimekar Health Center in Bogor Regency, 6 cases of undernutrition and malnutrition among toddlers were found.  One of the direct factors that can affect the nutritional status of toddlers is the intake of nutrients. Some macronutrients such as carbohydrates, fats, and proteins can increase the nutritional intake of toddlers. One of the strategies in addressing nutritional issues is the provision of supplementary nutrition. recovery program, which is one of the government's intervention programs for cases of malnutrition.  This program is specifically aimed at food-insecure groups. The purpose of this study is to determine the relationship between macro-nutrient intake and supplementary feeding on the nutritional status of toddlers aged 6-23 months.  This study uses a cross-sectional quantitative data collection method by applying simple random sampling techniques and involves 54 toddlers aged 6-23 months with inclusion criteria toddlers registered to receive recovery provision of supplementary nutrition, have a KIA book, and the respondent's mother is willing to participate in the study by filling out the informed consent.  Meanwhile, the exclusion criteria are toddlers suffering from physical disabilities, severe diseases (heart disease, kidney cancer, TB as medically diagnosed). Data collection was conducted through questionnaire interviews and a 2x24-hour food recall form, as well as measurements of weight and height.  The results of this study using the chi-square statistical test indicate that no significant relationship was found between the bivariate results of energy intake with a p-value of (0.936), protein intake with a p-value of (0.596), fat intake with a p-value of (0.353), carbohydrate intake with a p-value of (0.983), and supplementary feeding with a p-value of (0.643) on the nutritional status of toddlers. The conclusion of this study is that the intake of macronutrients and the provision of supplementary food are not related to the nutritional status of toddlers